1996
DOI: 10.1017/s0033291700034747
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin activity in anorexia nervosa after long-term weight restoration: response to D-fenfluramine challenge

Abstract: SYNOPSIS Abnormalities in central serotonin function have been implicated in the pathogenesis of anorexia nervosa. It is difficult, however, to separate neuroendocrine abnormalities induced by weight loss and malnutrition from those related primarily to the disorder itself. To minimize these influences, this study assessed long-term weight restored anorexics. A correlation between persistent eating-related psychopathology, co-morbid illness and serotonin dysfunction was sought. Nine female weight-restored out-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 30 publications
1
51
0
Order By: Relevance
“…The finding of significant depressive and anxiety symptoms in the ''weight-recovered'' AN group is in keeping with findings in other studies of ''weightrecovered'' AN, albeit mostly of 6-12 months' duration. [81][82][83] Participants in the AN and BN groups were chronically ill in terms of their mean illness durations. Although the inclusion criteria for the ''weight-recovered'' AN group required a minimum of 3 months at or above a BMI 18.5 kg/m 2 , the mean period of ''weight-recovery'' was 67.8 months (standard deviation 73.4 months) in keeping with longer-term periods of ''weight-recovery'' in other studies.…”
Section: Resultsmentioning
confidence: 99%
“…The finding of significant depressive and anxiety symptoms in the ''weight-recovered'' AN group is in keeping with findings in other studies of ''weightrecovered'' AN, albeit mostly of 6-12 months' duration. [81][82][83] Participants in the AN and BN groups were chronically ill in terms of their mean illness durations. Although the inclusion criteria for the ''weight-recovered'' AN group required a minimum of 3 months at or above a BMI 18.5 kg/m 2 , the mean period of ''weight-recovery'' was 67.8 months (standard deviation 73.4 months) in keeping with longer-term periods of ''weight-recovery'' in other studies.…”
Section: Resultsmentioning
confidence: 99%
“…First, studies of women who have recovered from an eating disorder avoid the confounding effects of malnutrition on 5-HT activity. Second, some, but not all studies, showed that a disturbance of 5-HT activity persists after recovery from an eating disorder (Kaye et al, 1991;O'Dwyer et al, 1996;Ward et al, 1998). Finally, certain behaviors, such as anxiety, perfectionism, and obsessionality, have been found to occur premorbidly, and persist after recovery from AN (Bulik et al, 1997;Casper, 1990;Deep et al, 1995;Srinivasagam et al, 1995;Strober, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] In fact, most studies have shown that individuals with AN have disturbances of central serotonin activity, [15][16][17] which persist after recovery. [18][19][20] The opioid system has been implicated in the modulation of feeding behavior in which opioid agonists and antagonists were injected into animals. [21][22][23][24] Some clinical studies have suggested that opioid antagonists may have beneficial effects on eating behavior symptoms in patients with eating disorders.…”
Section: Introductionmentioning
confidence: 99%